Tell el-Dab'a XXII : "Der Mund der beiden Wege" : Die Siedlung und der Tempelbezirk des Mittleren Reiches von Ezbet Ruschdi - Czerny, Ernst (Denkschriften der Gesamtakademie, 2015)
The final and comprehensive publication of the archaeological results of excavations by the Austrian Archaeological Institute at the site of Ezbet Rushdi (area "R/I") within the broader archaeological region of Tell el-Daba in the eastern Nil-delta. A Temple and a settlement site were investigated, both of Middle Kingdom origin